The Importance Of Use Of The Regional Language Malay Deli In Formal Education In Medan City - Napitupulu, Fenty Debora; Kusyani, Diah; Arfianty, Rani (Yayasan Insan Cipta Medan, 2023)
The aim is to hone regional language skills and develop students' personalities. It is our obligation as Indonesian citizens (WNI) to master and apply Indonesian in our daily lives properly and correctly, so that our regional languages maintain their authenticity. The aim of this research is to find out; 1) Understanding the language, 2) Indonesian language courses for students, 3) The importance of regional languages in formal education, 4) Aims and benefits of Indonesian language courses. So Indonesian is important to study in higher education, because Indonesian is a unifying language, a guide to the preparation and use of good and correct language in scientific communication, as well as to deepen the language in communication and to be preserved by native speakers.